2021
DOI: 10.1016/j.kint.2021.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in pediatric patients hospitalized with acute COVID-19 and multisystem inflammatory syndrome in children associated with COVID-19

Abstract: This study describes the incidence, associated clinical characteristics and outcomes of acute kidney injury in a pediatric cohort with COVID-19 and Multisystem Inflammatory Syndrome in Children (MIS-C). We performed a retrospective study of patients 18 years of age and under admitted to four New York hospitals in the Northwell Health System interned during the height of the COVID-19 pandemic, between March 9 and August 13, 2020. Acute kidney injury was defined and staged according to Kidney Disease: Improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 31 publications
4
65
1
13
Order By: Relevance
“…Scarce histological data are available, showing in most cases ATN, collapsing glomerulopathy or TMA in patients with acute COVID-19 infection ( 18 22 ). AKI is also common during MIS-C, ranging from 10% to 60% of the cases ( 6 , 23 , 24 ) while it was described in four adults in a case series of 20 MIS-A with cardiac involvement ( 12 ). Currently, the pathogenesis of AKI in MIS is thought to be mainly related to cytokine-mediated hypotension and cardiac dysfunction, leading to renal hypoperfusion ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scarce histological data are available, showing in most cases ATN, collapsing glomerulopathy or TMA in patients with acute COVID-19 infection ( 18 22 ). AKI is also common during MIS-C, ranging from 10% to 60% of the cases ( 6 , 23 , 24 ) while it was described in four adults in a case series of 20 MIS-A with cardiac involvement ( 12 ). Currently, the pathogenesis of AKI in MIS is thought to be mainly related to cytokine-mediated hypotension and cardiac dysfunction, leading to renal hypoperfusion ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that COVID-19 affects the endothelial system, leading to endothelial dysfunction characterised by a pro-inflammatory and procoagulative state (2)(3)(4)(5). Clinical series of Kawasaki-like multisystem inflammatory syndrome (MIS), occurring after viral clearance, have been described in children (MIS-C) (6)(7)(8)(9). Recently, similar case Abbreviations: aHUS, atypical haemolytic uremic syndrome; AKI, acute kidney injury; BMI, body mass index; CFB, Complement factor B; CFH, Complement factor H; CFI, Complement factor I; MCP, Membrane Cofactor Protein; CRP, C-reactive protein; hsTroponin, high-sensitivity troponin; MAC, membrane attack complex; MIS-C, multisystem inflammatory syndrome in children; MIS-A, multisystem inflammatory syndrome in adults; PCR, polymerase chain reaction; RRT, renal replacement therapy; sCr, serum creatinine; sC5b-9, soluble C5b-9; TMA, thrombotic microangiopathy; THBD, Thrombomodulin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKI developed at admission in most of them which were associated with lower serum albumin levels and higher white blood cell counts. 47 Two out of 9 MIS-C patients recently reported from Germany had unusual findings. One developed encephalomyelitis.…”
Section: Clinical Featuresmentioning
confidence: 95%
“…In this issue of Kidney International, Basalely et al do just that by providing additional data on the incidence, clinical characteristics, and outcomes of COVID-19 in a cohort of 152 children (aged <18 years) who were admitted to 4 New York hospitals during the height of the COVID-19 pandemic. 5 AKI developed in 11.8% (18 patients) of this cohort (combined acute COVID-19 and multisystem inflammatory syndrome in children [MIS-C]) and completely resolved in 83% of them. These findings are in contrast to a crosssectional point prevalence study of AKI in COVID-19 patients that reported the development of AKI in nearly half (44%) of 106 children admitted to ICUs in 41 centers, 32 of which were United States based.…”
mentioning
confidence: 99%